Experimental study of current-sheet-like structure in pinching plasma flows with electric and magnetic probes - Volkova, Yu.Ye.; Solyakov, D.G.; Marchenko, A.K.; Ladygina, M.S.; Petrov, Yu.V.; Chebotarev, V.V.; Merenkova, T.M.; Makhlai, V.A.; Yeliseyev, D.V.; Staltsov, V.V. (Problems of Atomic Science and Technology, 2022)
The formation of the current-sheet-like structure under the influence of the external magnetic field in pinching plasma flows generated by the magnetoplasma compressor has been studied. A set of magnetic and electric probes were used to measure the self-generated magnetic field, electron temperature, and electric field locally with sufficiently high temporal and spatial resolution. The data obtained from the probe measurements were used to plot the spatial distributions of electric current and drift velocity in the plasma stream to identify the patterns of plasma flow. In the presence of external magnetic field, the current density, electron temperature, and the ion saturation current reach a peak in close proximity to the sheet. Measurements indicate the outflow of two electron jets of different temperatures from the layer. Досліджено формування структури типу струмовий шар під впливом зовнішнього магнітного поля в самостиснених потоках плазми, що генеруються магнітоплазмовим компресором. Магнітні та електричні зонди використовувалися для локального вимірювання власного магнітного поля, електронної температури й електричного поля з достатньо високою часовою і просторовою роздільною здатністю. Дані, які отримані в результаті зондових вимірювань, були використані для побудови просторових розподілів електричного струму та швидкості дрейфу в потоці плазми для виявлення особливостей потоку плазми. За присутності зовнішнього магнітного поля густина електричного струму, електронна температура та іонний струм насичення досягають максимуму в безпосередній близькості від шару. Вимірювання свідчать про витік із шару двох електронних пучків із різними температурами.